2005
DOI: 10.1158/1078-0432.ccr-05-0014
|View full text |Cite
|
Sign up to set email alerts
|

CCR7 and CXCR4 as Novel Biomarkers Predicting Axillary Lymph Node Metastasis in T1 Breast Cancer

Abstract: Purpose:The chemokine receptors CCR7 and CXCR4 have been shown to play an important role in cancer metastasis.We therefore studied the differential expression of CCR7 and CXCR4, along with that of the biomarker HER2-neu, to evaluate whether these biomarkers could predict axillary lymph node metastasis in breast cancer. Experimental Design: Biomarker expression levels were evaluated using paraffin-embedded tissue sections of lymph node^negative (n = 99) and lymph node^positive (n = 98) T 1 breast cancer by immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
191
4
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(226 citation statements)
references
References 32 publications
25
191
4
6
Order By: Relevance
“…The accuracy of lymph-node evaluation influences clinicians' choice of the appropriate therapeutic regimen and most likely prognosis (Fisher et al, 1983;Jatoi et al,1999;. In recent years, many sensitive methods have been developed to detect micro-metastasis in lymph nodes, e.g., immunohistochemical (Cabioglu et al, 2005;Denninghoff et al,2008;Thongwatchara et al, 2011;Yenidunya et al,2011) and molecular biological techniques. However, the role of micro-metastasis in clinical outcome is under extensive study.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of lymph-node evaluation influences clinicians' choice of the appropriate therapeutic regimen and most likely prognosis (Fisher et al, 1983;Jatoi et al,1999;. In recent years, many sensitive methods have been developed to detect micro-metastasis in lymph nodes, e.g., immunohistochemical (Cabioglu et al, 2005;Denninghoff et al,2008;Thongwatchara et al, 2011;Yenidunya et al,2011) and molecular biological techniques. However, the role of micro-metastasis in clinical outcome is under extensive study.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CXCR4 has been reported in more than 23 different types of cancer cell [137]. The accumulating evidence suggests that CXCR4 is an important regulator of breast cancer metastasis and can be predictive of lymph node metastasis [138][139][140]. In experimental studies, treatment of CXCR4-expressing breast cancer cells with neutralizing anti-CXCR4 antibody reduced metastasis to lung in a mouse model [133].…”
Section: Chemokines and Their Receptors In Tumor Growth And Metastasismentioning
confidence: 99%
“…In oesophageal cancer and melanoma, CXCR4 expression is associated with poor clinical outcome [147,148]. In breast cancer, CXCR4 expression predicted lymph node metastasis [138]. Patients with high CXCR4 expression in NSCLC, colorectal or prostate cancer were more prone to metastasis [149][150][151].…”
Section: Chemokines and Their Receptors In Tumor Growth And Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that cancer cells can respond to chemokine stimuli through expression of their respective receptors [6] , altering cancer cell invasive and metastastic properties. Elevated levels of CXCR4 and CCR7 in breast carcinoma are significantly associated with increased malignancy, advanced disease and poor prognosis [7][8][9][10][11] . In breast cancer, CXCR4 expression increases progressively with increasing malignant potential [10] , and CCR7 is associated with lymph node metastasis [11] .…”
Section: Introductionmentioning
confidence: 99%